Quality of Learning during the Pandemic based on cognitive and affective aspects in Indonesia - Muhammad Aulia Ramadhana; Kiki Nofita Hani; Desy Andri Tri Palupi; Bagas Pradypta (Basic and Applied Education Research Journal, 2020)
Learning problems were found during the Covid 19 pandemic. Measuring the quality of learning is very important to overcome these problems. This study aims to analyze the quality of learning during the pandemic based on cognitive and affective aspects. This study uses qualitative descriptive research methods. The use of qualitative descriptive methods in the study aims to describe phenomena that focus on interrelationships between activities. The purposive sampling was used, which is based on provinces with high covid 19 cases in Indonesia. The results showed that the quality of learning decreased because students did not have learning motivation. Many obstacles are experienced during learning related to school unpreparedness to measure students' cognitive and affective abilities. The use of technology that has not been optimal is one of the causes of this problem. The quality of distance learning during the pandemic was low due to school facilities and limited teacher skills in utilizing learning media. Keywords:Quality of learning, Pandemic period, Indonesia